Highlights from the 2018 European Respiratory Society Congress presentations on interstitial lung diseases - Alfaro, Tiago M.; Afonso, Margarida; Torrisi, Sebastiano Emanuele (Journal of Thoracic Disease; Vol 10, Supplement 25 (September 2018): Journal of Thoracic Disease [Dedicated to the 28th International Congress of the European Respiratory Society (ERS 2018)], 2018)
Interstitial lung diseases (ILDs) are a large and heterogeneous group of lung disorders characterized by primary involvement of the lung interstitium. Several studies point out their increasing incidence and global burden leading to a growing interest and massive literature production in the last few years.